Análise da matriz energética e econômica das culturas de arroz, soja e trigo em sistemas de produção tecnificados no Rio Grande do Sul - Ferreira, Fernanda de Figueiredo (2011)
The energy analysis aims to compare the performance between productive units and activities, searching an approach to link the energy with the economic, social and cultural parameters in the management of natural resources in economic systems. The main question that arises and guides this dissertation is the analysis of the energy produced and consumed during the production process of major crops in the state of Rio Grande do Sul, namely, rice, soybeans and wheat, opposed to the economic results of such activities. The research was exploratory and based on multi-case studies with the use of literature review, laboratory analysis and interviews with producers. The choice of the production units studied favored the production systems that adopt modern technologies, where precision agriculture and controlled use of natural resources, such as water, are developed. Calculations were performed considering the energy available with workforce, seeds, fertilizers and pesticides (herbicides, insecticides and fungicides) machinery and equipment as well as fuels (lubricating oils, greases and diesel). To obtain the results of economic activities the added-value theory was used. The results demonstrate that the activity of soybean in no-tillage system with crop rotation achieved the highest energy efficiency between 25.58 MJ.ha-1 and 38.39 MJ.ha-1, whereas wheat culture showed the lowest efficiency with 3.13 MJ.ha-1. Regarding the economic performance of crops, soybeans showed the highest economic efficiency 2,47 and wheat the lowest 1,14. It is worth mentioning the significant economic results achieved by the rice crop, expressed by the high added-value obtained per unit area (VAL/ha R$ 3,802.00) due to its high physical productivity. In spite of having positive energy indicators, significant expenses on fertilizer, fuel and pesticides were observed in all properties studied. Thus, we reinforce the importance of the debate on social and environmental sustainability of the systems studied, especially when analyzed from the perspective of energy expenses of non-renewable resources and social problems attributed to workforce.